THE EFFECT OF PROJECT BASED LEARNING MODEL TO STUDENT CREATIVITY IMPROVEMENT ON WASTE RECYCLING PRODUCT MATERIAL - Dini Afriansyah; Fajri Ismail; Erie Agusta; Muhammad Nasrul Mustain (Al 'Ilmi : Jurnal Pendidikan MIPA, 2017)
This study aims to determine the effect of project based learning models to increase students’ creativity inwasterecycling products of class X. The sample of this research is students at class X. X.1as a experimental classwith 30 students and class X.2 asa control class with 30 students. Data obtained from the documentation, studentsactivity sheets, product creativity assessment sheets, and students creativity questionnaire. The data analysis usedis the result of prerequisite test data and hypothesis test which includes independent sample t- test and pairedsample t- test. The results show that Ha of both hypothesis tests are accepted. This means that Project BasedLearning model influences students' creativity in making waste recycling products at class X. Keywords :project based learning, student creativity increasing, waste recycling product